(untitled) (Aura: Journal for the Study of New Religions, 2021)
Research on the early 20th century European and American reception of yoga have revealed the significance of esoteric movements like the Theosophical Society in creating the modern, global phenomenon of yoga. Alongside interpretations of yoga as primarily a form of meditation which were common in the literature and, sometimes practice, of movements like Theosophy or Thelema there exist another phenomenon labeled yoga that have received less attention. A system of pedagogy called raja yoga was for several decades among the foremost preoccupations of one of the main global Theosophical movements, the Universal Brotherhood. Under its leader Katherine Tingley, the Universal Brotherhood strove to develop and popularize raja yoga as the solution to the social and spiritual problems of humanity. Focusing on Swedish raja yoga literature of the Universal Brotherhood, this article will explore how Swedish writers imagined and argued for this system of education and spiritual development. Furthermore, the article will investigate some of the complicated connections between this form of pedagogy and the broader trends of the early 20th century European reception of yoga.